Family composition and children's dental health behavior: evidence from Germany - Listl, Stefan (Journal of public health dentistry, 2011)
Objective: To assess whether children's dental health behavior differs between family compositions of either natural parents or birth mothers together with stepfathers. Methods: We use data from the German Health Interview and Examination Survey for Children and Adolescents (KiGGS) public use file. This is the first nationally representative sample on child health in Germany and particularly contains variables for dental attendance, tooth care, and eating behavior of 13,904 children below 14 years of age. A series of zero-inflated Poisson, ordinary least squares, binary, and ordered logistic regression models was set up in order to identify whether family composition is a significant explanatory variable for children's dental health behavior. Results: Family composition turned out as a significant parameter for some aspects of children's dental health behavior. Specifically, children who grow up in families with a birth mother and a stepfather have only half the probability to access dental services but, once seeking treatment, the number of visits is significantly higher in comparison with children raised by their natural parents. Moreover, children growing up in such a patchwork family setting consume a higher amount of sugary foods and drinks. This appears mainly attributable to differential consumption habits for juices, cookies, and chocolate. Conclusions: Children who grow up in settings other than the nuclear family may develop different dental health behaviors than children who grow up with both natural parents, albeit more research is needed to identify the extent to which such behavioral changes lead to variations in caries occurrence.
Gesehen am 19.09.2022